BELATED MEMORY AND THE DUAL FUNCTION OF FORGETTING AS PROTECTION AND REPRESSION IN SHAPING CHARACTER BEHAVIOR IN KAZUO ISHIGURO'S THE BURIED GIANT - Amelia Sekar Maharani; Zuhrul Anam (CALL, 2026)
This study examines the role of memory and forgetting in The Buried Giant through the lens of trauma theory, in which memory emerges as a delayed and disruptive return of unassimilated experience. While previous studies emphasize collective memory, limited attention has been given to how belated memory reshapes individual behavior. Drawing on Cathy Caruth's concept of belated experience, this study analyzes whether forgetting functions as a protection or repression and how remembering transforms emotional responses and relationships. Using qualitative textual analysis and close reading of key narrative events, the study focuses on the function of forgetting and whether remembering changes the behavior of Axl, Beatrice, Wistan, and Sir Gawain. The findings show that forgetting functions simultaneously as psychological protection and political repression: it preserves emotional stability at the personal level while suppressing unresolved historical violence at the collective level. However, the return of memory destabilizes both domains, reshaping identity, moral perception, and relational dynamics. This study demonstrates that remembering does not simply recover the past but reconfigures the present, exposing the ethical tension between peace sustained through forgetting and truth revealed through memory. These findings contribute to trauma and memory studies by highlighting the complex role of forgetting as both a stabilizing and destabilizing force in post- conflict narrative. By foregrounding the behavioural consequences of belated memory, this study highlights how Ishiguro’s narrative problematizes reconciliation built on enforced forgetting.